Islamic Social Entrepreneurship as a Catalyst for Poverty Alleviation: A Qualitative Study on Community-Based Empowerment - Amir Mukadar; Dharma Setiawan (Journal of Social and Humanities, 2024)
Islamic social entrepreneurship has gained increasing attention as a value-based approach to poverty alleviation in Muslim-majority societies. However, limited empirical research has examined how Islamic social enterprises translate religious values into governance practices, empowerment mechanisms, and sustainable community development. This study investigates Islamic social entrepreneurship as a mechanism of community-based empowerment in Bengkulu Province, Indonesia. Using an interpretivist qualitative approach and a multi-site case study design, data were collected from six Islamic social enterprises through semi-structured interviews, field observations, and documentary analysis. A total of 34 participants were involved, comprising enterprise practitioners, community beneficiaries, religious leaders, and local government representatives. Thematic analysis identified four major findings. First, Islamic ethical values such as falah, maslahah, amanah, and ‘adl shaped enterprise governance when they were institutionalised in decision-making, accountability, and resource allocation. Second, empowerment emerged as a multidimensional process involving economic capability, social recognition, moral legitimacy, and community participation. Third, Islamic social enterprises faced persistent tensions between social mission, financial viability, and Shari’a-compliant operational models. Fourth, regulatory ambiguity, limited access to Islamic capital, and managerial capacity gaps constrained institutional sustainability and scalability. The study contributes to Islamic social entrepreneurship literature by demonstrating that religious values become transformative only when embedded in participatory governance, sustained mentoring, and supportive institutional ecosystems.